Ultrastructural and proteomic evidence for the presence of a putative nucleolus in an Archaeon - Islas-Morales, Parsifal F.; Cárdenas, Anny; Mosqueira, María J.; Jiménez-García, Luis Felipe; Voolstra, Christian R. (Frontiers in Microbiology, 2023)
Nucleoli are subcellular compartments where transcription and maturation of pre-ribosomal RNAs occur. While the transcription of ribosomal RNAs is common to all living cells, the presence and ultrastructure of nucleoli has been only documented in eukaryotes. Asgard-Archaea are the closest prokaryotic relatives of eukaryotes and their near relatives, TACK-Archaea, have homologs of nucleolar proteins and RNAs in their genome, but the cellular organization of both is largely unexplored. Here, we provide ultrastructural and molecular evidence for the presence of putative nucleolus-like subcellular domains in the TACK crenarchaeon Saccharolobus solfataricus (formerly known as Sulfolobus solfataricus). Transmission electron microscopy (TEM) revealed consistent electron-dense fibro-granular compartments, also positive to the specific silver staining for nucleolar organizer regions (AgNOR). TEM also confirmed that ribosomal DNA (rDNA) is spatially distributed in non-random, clustered arrays underlying fine structures, as observed by ultrastructural in situ hybridization. To further explore these initial observations, proteomic sequencing of isolated bands from AgNOR-stained protein gels was conducted and compared against a compiled inventory of putative nucleolar homologs from the S. solfataricus P1 genome. Sequenced AgNOR-sensitive peptides encoded homologs of eukaryotic nucleoli proteins, enriched for nucleolus-related functions. Together with the identification of non-argyrophilic nucleolar homologs in the P1 genome, we propose a model for a putative nucleolus in S. solfataricus. Our data provide initial evidence that subcellular domains of nucleolar-like nature are not exclusive to eukaryotes. Whereas technical limitations and new aspects remain a matter for future functional studies, our data may be useful to think of the origin of nucleoli within the common ancestor of Eukarya and TACK-Archaea, based on a two-domain tree of life.